Co(II),Cu(II),Ni(II),Fe(II)and Cr(III) Complexes of N,O-Type Schiff base ligand derived from 4,4,-methylenedianiline Synthesis, Characterization and antibacterial studies - N. Deneef , Suror; A. Mehdi, Hiader (University of Thi-Qar Journal of Science, 2019)
Complexes of Co(II),Cu(II),Ni(II),Fe(II)and Cr(III) were prepared from reaction between (E)-2-(((4-(4-aminobenzyl)phenyl)imino)methyl)phenol and hydrated metal ions such as CoCl2.6H2o,NiCl2.6H2O.FeCl2.6H2O and CrCl3.H2O characterization by analytical and spectra chemical methods .the metal:ligand stoichiometric ratio is 1:1 n the all complexes.it was determined that bidentate behavior of the ligand is accomplished via the phenolic oxygen and the azomethine nitrogen atom .the presence of water revealed by thermogram and supported by the presence of relevant bonds in their IR Spectra. These new complexes showed areasonable amount antibacterial activity.a ligand was synthesized by reaction (4,4'-Methylenedianiline and Salicylaldehyde. The newly synthesized compounds were characterized by Fourier Transform Infrared (FTIR) Spectroscopy, Nuclear Magnetic Resonance Spectroscopy (1H NMR), elemental analyses (C, H, N), mass spectral, conductivity measurement, magnetic sensitivity measurement and atomic Absorption. The mass spectrum of the ligandexhibits a molecular ion peak [M]+.at 302 m/z.